2014
DOI: 10.4238/2014.february.27.14
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the reversal effect of mifepristone on drug resistance of the human cervical cancer cell line HeLa/MMC

Abstract: ABSTRACT. We examined the ability of mifepristone to reverse the in vitro drug resistance of human cervical cancer cells resistant to mitomycin-C (HeLa/MMC) cells and investigated the mechanism of this effect. A 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay was performed to detect the drug resistance of HeLa/ MMC cells and the reversed drug resistance in vitro. Expression levels of B-cell lymphoma 2 (Bcl-2), Bcl-2-associated X protein (Bax), and glucosylceramide synthase (GCS) were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…2009 ). More recently, a reversal of the resistance to mitomycin-C by mifepristone has been described in HeLa cells ( Chen et al . 2014 ).…”
Section: Cervical Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…2009 ). More recently, a reversal of the resistance to mitomycin-C by mifepristone has been described in HeLa cells ( Chen et al . 2014 ).…”
Section: Cervical Cancermentioning
confidence: 99%
“…In the endometrial cell line EM42, mifepristone stimulated the activity of the transcription factor nuclear factor kappa B (NFkB) and induced apoptosis mediated by the induction of pro-apoptotic Bax and downregulation of antiapoptotic Bcl2, in a NFkB-dependent manner ( Han & Sidell 2003 ). In HeLa cervical adenocarcinoma cells resistant to mitomycin C, mifepristone increased BAX expression while decreasing expression of BCL2 ( Chen et al . 2014 ).…”
Section: Mechanisms Of Growth Inhibition Driven By Antiprogestinsmentioning
confidence: 99%
“…Studies by Chen et al and by Jurado et al both reported that MIF could reverse the drug resistance of HeLa cells by increasing Bcl-2 protein expression and reducing Bax protein expression. In addition, the overexpression of glucosylceramide synthase may play a crucial role in the development of MDR in cervical cancer cells and can be induced by MIF [19,20]. Additional studies have shown that by altering the expression of Bcl-2 and Bax, MIF changes the mitochondrial permeability and causes release of Omi/HtrA2 protein, which subsequently antagonizes inhibitor of apoptosis proteins (IAPs).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, metapristone (RU42633) is the primary metabolite of mifepristone (RU486) [14], which is used to terminate pregnancy in the rst month in clinic [15]. Some reports had showed that metapristone could inhibit lots of cancer cell proliferation [16,17]. However, there were few reports that indicated that whether metapristone could treat endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%